Case Report: Defect repair post-resection of cervical tracheal granular cell tumor by cervical anterior banded myofascial flap: A case study and literature review - Liu, Zhu; Li, Zhendong (Frontiers in Oncology, 2023)
Objective: A case of cervical tracheal granular cell tumor (CTGCT) is reported together with a discussion on the clinical manifestation, diagnosis, and treatment of CTGCT. Additional cases of tumors in the tracheal membrane are also discussed. A simple and viable tracheal reconstruction method was proposed. The research design involves a case report and literature review. Methods: Twenty-four case reports on cervical GCT with complete clinical data were identified, with a specific focus on cases involving surgical treatment of tumors in the cervical tracheal membrane. Results: Twenty-eight reports of GCT in the cervical trachea and six reports on cervical tracheal membrane tumors were identified. The clinical data of a middle-aged Asian woman with a cervical GCT was also discussed. Conclusion: Cervical GCT is a rare disease, and tracheal resection is a reasonable treatment for cervical tracheal GCT. The proposed procedure is a simple and feasible method for reconstruction of the cervical tracheal membrane defect using a double-pedicled banded myofascial flap.